Вивчення ролі іонів в процесах запалювання та горіння газових сумішей в Україні (перша половина ХХ сторіччя) - Сюх, А.В. (Питання історії науки і техніки, 2009)
Рассмотрена деятельность научных лабораторий Днепропетровского горного и физико-технического институтов в области физики горения и взрывов в первой половине ХХ столетия. Проанализированы результаты исследований отечественных ученых по изучению роли заряженных частиц в процессах зажигания и горения взрывных газовых смесей. It was considered the activity of scientific laboratories of Dnipropetrovs’k in the Mountain
and Fiziko-technical institutes in the first half of ХХ century. It was analyzed the results of
investigation of home scientists on the study of role of the charged particles in the processes of
lighting and burning of explosive gas mixtures.